Antioxidants in Shell and Nut Yield Components after Ca, Mg and K Preharvest Spraying on Hazelnut Plantations in Southern Chile - Carlos Manterola-Barroso; Karina Godoy; David Alarcón; Daniela Padilla; Cristian Meriño-Gergichevich (Plants, 2022)
To determine the effects of pre-harvest calcium (Ca), magnesium (Mg) and potassium (K) spraying on the antioxidant activity and capacity of hazelnut (Corylus avellana L.) shells, as an approach to sustain the utilization of the main residue derived from this industry, four commercial hazelnut (Tonda di Giffoni) orchards located in Southern Chile (Cunco, Gorbea, Perquenco and Radal), during the 2018/19 season were sprayed three times with five combinations of Ca (300 and 600 mg L−1), Mg (300 and 600 mg L−1) and K (300 and 600 mg L−1). Yield components were determined in harvested whole nuts, whereas Ca, Mg and K concentrations, as well as total phenolic compounds, free radical scavenging antioxidant activity, and oxygen radical absorbance capacity, were determined in shells. All spray treatments with both Ca, Mg and K combinations showed a significant interaction between locality and treatment (L × T) on increased stabilized nut yield (kg ha−1) in comparison with the control treatments, whereas nut quality was differentially affected by treatment and orchard locality, thus confirming a significant L × T relationship regarding nut length and kernel yield. However, locality showed a major effect on kernels and shells. A significant relationship was determined between locality and the Ca, Mg and K spraying (L × T) concerning antioxidant compounds such as phenolics, whose amounts exceeded those of the control treatments by three times. Antioxidant capacity and activity in shells showed a significant L × T relationship, and nutshells collected from Cunco showed remarkably (3–4 times) higher levels of these factors than the other evaluated localities. Interactions between spray treatment and orchard location were responsible for the different values obtained in the experiments, confirming the influence of the environment on the efficacy of the treatments. Finally, these shells are worth further study as an interesting residue of the hazelnut industry due to their nutritional and antioxidant properties.